Phase diagram of the Ba(Fe1?x Cox )2 As2 single crystal grown from In flux - Garitezi , Thales Macedo (Physicae Proceedings, 2020)
The interplay between magnetism and superconductivity in the iron arsenide superconductors have generated great interest in past years. Here we present the growth and characterization of Ba(Fe1?x Cox )2 As2 single crystals grown from In-rich flux, which represents an alternative to the conventional self-flux method. This method does not require excess Fe or As, which the latter is a danger to the grower. The crystals have dimensions up to 2.0 × 2.0 × 0.05 mm3 . They were characterized by electrical resistivity, magnetic susceptibility, specific heat and X-ray diffraction measurements. The determination of the transition temperatures allowed the construction of the phase diagram for this series. The obtained phase diagram is confronted with the ones in literature.